PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK RELIGIUSITAS SISWA KELAS IV DI SDN 2 PENGARAYAN - Syarnubi Syarnubi (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
This study aims to describe and analyze critically the professionalism of teachers in the form of PAI religiosity fourth grade students at SDN 2 Pengarayan. This research is a qualitative research taking the location of SDN 2 Pengarayan. Data collection are getting by observation, documentation and interIVews. Data analysis were carried out by examining all data, data reduction, data presentation, drawing conclusions and verifying data. Data checking is done by triangulation with two modes, namely using multiple sources and multiple methods. The results of the study show: (1) PAI teachers in SDN 2 Pengarayan are professional, which is indicated by haIVng four competencies: pedagogic competency, personality competence, professional competence and social competence. (2) PAI teachers is forming the religiosity of fourth grade students in SDN 2 Pengarayan through five dimensions of religiosity (Belief, worship, appreciation, knowledge and experience), using habituation methods related to four competencies as follows : Pedagogical aspects: Prepare syllabus and lesson plans. Personality Aspect: Making the dhuhur prayer schedule in congregation and assistance, praying duha and reciting the Asmaul Husna. Professional Aspects: BATUHA (Read Write Al-Qur'an), PHBI (Commemoration of Islamic Day) and Muadzin. Social Aspects: Making Tambourine Music Group, Ramadhan pesantren and habit of greeting. (3) The obstacles faced by PAI teachers in forming the religiosity of students in SDN 2 Pengarayan are the limitations of place, time and superIVsors, the low support of parents when at home, the lack of harmonious cooperation between parents of students and the school, the cleanliness of places of worship become an obstacle in the implementation of prayer serIVces.